A prototype photoplethysmography-based cuffless device shows promising results in tracking changes in blood pressure - Hove, Christine; Sæter, Frode Wirum; Stepanov, Alexey; Bøtker-Rasmussen, Kasper Gade; Seeberg, Trine M.; Westgaard, Espen; Heimark, Sondre; Waldum-Grevbo, Bård; Hisdal, Jonny; Larstorp, Anne Cecilie K. (Frontiers in Medical Technology, 2024)
Introduction Non-invasive cuffless blood pressure devices have shown promising results in accurately estimating blood pressure when comparing measurements at rest. However, none of commercially available or prototype cuffless devices have yet been validated according to the appropriate standards. The aim of the present study was to bridge this gap and evaluate the ability of a prototype cuffless device, developed by Aidee Health AS, to track changes in blood pressure compared to a non-invasive, continuous blood pressure monitor (Human NIBP or Nexfin) in a laboratory set up. The performance was evaluated according to the metrics and statistical methodology described in the ISO 81060-3:2022 standard. However, the present study is not a validation study and thus the study was not conducted according to the ISO 81060-3:2022 protocol, e.g. non-invasive reference and distribution of age not fulfilled. Method Data were sampled continuously, beat-to-beat, from both the cuffless and the reference device. The cuffless device was calibrated once using the reference BP measurement. Three different techniques (isometric exercise, mental stress, and cold pressor test) were used to induce blood pressure changes in 38 healthy adults. Results The mean difference (standard deviation) was 0.3 (8.7) mmHg for systolic blood pressure, 0.04 (6.6) mmHg for diastolic blood pressure, and 0.8 (7.9) mmHg for mean arterial pressure, meeting the Accuracy requirement of ISO 81060-3:2022 (< 6.0 (10.0) mmHg). The corresponding results for the Stability criteria were 1.9 (9.2) mmHg, 2.9 (8.1) mmHg and 2.5 (9.5) mmHg. The acceptance criteria for the Change requirement were achieved for the 85th percentile of  50% error for diastolic blood pressure and mean arterial pressure but were higher than the limit for systolic blood pressure (56% vs < 50%) and for all parameters for the 50th percentile (32-39% vs < 25%). Conclusions The present study demonstrated that the cuffless device could track blood pressure changes in healthy adults across different activities and showed promising results in achieving the acceptance criteria from ISO 81060-3:2022.